Some critical factors in personal financial planning - P. W.C. De Wit (South African Journal of Business Management, 1989)
The use of effective financial planning is often neglected by private individuals. In the inflationary environment of today the lack of financial planning can lead to financial disaster, especially when a person reaches his or her retirement age. This article reports the results of a study regarding financial planning by private individuals. It highlights the different levels of wealth obtained and some of the methods used in obtaining those levels of wealth. An effort is made to give advice to the individual in order to curb the statement so often heard: 'If I were a rich man'.
Keywords: 650